2022
DOI: 10.1002/jmri.28299
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Cardiac Magnetic Resonance Reference Values for Biventricular Volumes Derived From Different Contouring Techniques

Abstract: Background Measurement of ventricular volumes and function using MRI is an important tool in pediatric congenital heart disease. However, normal values for children are sparce and analysis methods are inconsistent. Purpose To propose biventricular reference values in children for two MRI postprocessing (contouring) techniques. Study Type Retrospective. Subjects A total of 154 children from two institutions (13.9 ± 2.8 years; 101 male) that were referred for a clinical MRI study. Field Strength/Sequence 1.5 T; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
(78 reference statements)
1
5
0
Order By: Relevance
“…Regression results from this study show that height is strongly associated with RV volumes compared to other anthropometric or demographic parameters. Similar results were shown in a recently published study from our group in a cohort of healthy children and adolescents that showed that particularly height but also weight showed strong associations with ventricular volumes [12] . Furthermore, It is known that extreme weight (obesity or underweight) can affect CMR results [19] .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Regression results from this study show that height is strongly associated with RV volumes compared to other anthropometric or demographic parameters. Similar results were shown in a recently published study from our group in a cohort of healthy children and adolescents that showed that particularly height but also weight showed strong associations with ventricular volumes [12] . Furthermore, It is known that extreme weight (obesity or underweight) can affect CMR results [19] .…”
Section: Discussionsupporting
confidence: 91%
“…Height or the calculation of the ideal BSA might therefore be more appropriate for indexing of CMR-derived volumetric measurements [19] . Taking into account these consideration, our results [12] , and research from other groups [19] , [21] , it was decided to create reference curves and tables with respect to body height of HLHS patients. RV mass, however, was most strongly associated with patient age suggesting that time might be more important for RV myocardial changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current issue of JMRI, Voges et al 8 present cardiac biventricular reference values for the above discussed, two different segmentation methods, in a study of 154 healthy children who had undergone 1.5T cardiac MRI. The authors analyzed short‐axis cine images and derived EDV, ESV, ejection fraction, and end‐systolic and end‐diastolic myocardial mass for both LV and RV.…”
mentioning
confidence: 99%
“…Ejection fraction was relatively normal in these subjects but might affect results. Age, BSA, contouring technique (trabeculae or not), and gender may affect ventricular evaluation, 9 and further exploration of those factors would also be welcome.…”
mentioning
confidence: 99%